ADULT EDUCATION AS A PANACEA FOR HIV/AIDS STIGMATIZATION IN NIGERIA - Hussain, Muhammad Shehu (Sokoto Educational Review, 2013)
The main purpose of adult education is basically to help improve the status of people especially the disadvantaged to enable them to participate actively in the development of their respective communities and society in general. Stigma is a sign of social unacceptability or shame or disgrace attached to something, the essence is for people living with HIV/AIDS to live free from discrimination and inclined to declare and acknowledge their health status. It is against this background that the paper suggested that adult education programmes like literacy education, health education amongst others are capable for providing a solution in order to ameliorate the scourge of stigma from people living with HIV/AIDS.